UNDERSTANDING PUBLIC SERVICE ETHICS IN PERSPECTIVE THE NEW PARADIGM OF PUBLIC ADMINISTRATION - HJ. Sukmiah (P3M Stia Al Gazali Barru and Meraja media, 2021)
This study aims to provide an overview in understanding public service ethics according to the perspective of the new administrative paradigm so that it can be taken into consideration in the implementation of public services in Indonesia. The type of research used is a qualitative research type. Data collection techniques were carried out through a review of literature, literature, scientific journals and statutory documents that were collected to find their relevance to the research theme. The results show that public service ethics in a new paradigm of public administration such as the New Public Service (NPS) that can be used as a reference by bureaucrats is where bureaucrats in carrying out their duties and functions are considered good or ethical if they are responsible and have high professionalism or competence. and have responsibility in carrying out their duties and authorities. Service personnel must also pay attention to efficiency, effectiveness and economy. equality and justice. The most important of a public service is the fulfillment of the needs of the public being served so as to create satisfaction for the community. What is expected in public service ethics according to the new public service (NPS) paradigm is the emergence of self-awareness of bureaucrats based on the norm values in the code of ethics. From that, the most important thing is the awareness of the service apparatus that the service tasks carried out are not only accountable to the people and the state, but also to God Almighty.